Assessment of barriers for midwives to achieve professional management positions from midwives' point of view - Razieh Pourkazemi; Marjan Beigi; Shahnaz Kohan (Wolters Kluwer Medknow Publications, 2017)
Background: Despite the effects of midwives on the health of family and community through promotion of maternal and child health indicators, they are not in the position of professional decision making. Therefore, this study was aimed to determine the barriers to achieve professional management positions by midwives. Materials and Methods: This study was a descriptive and cross-sectional study. The members of board commission of midwifery and reproductive health, the academic members of midwifery department and midwives working at the adjutancy of health and treatment were selected from eight Iranian universities of medical sciences. Data was collected through demographic characteristics questionnaire, a researcher-made questionnaire about administrative barriers, and management skills. Validity and reliability of this tool was confirmed through content validity and Cronbach's alpha coefficient, and the results were analyzed using inferential statistics (analysis of variance and Kruskal-Wallis test). Results: The results of this study showed that the barriers for midwives to achieve professional management positions in order of preference were organizational barriers (71.4%), cultural barriers (42.4%), and individual barriers (30.8%). Conclusions: Based on the findings of this research, organizational barriers are the most important obstacle to achieve professional management positions. Therefore, the role of the authorities is emphasized to eliminate organizational barriers and provide more resources to reduce this problem.